Collaborative Problem Based Learning Integrated with Online Learning - Hendarwati, Endah; Nurlaela, Luthfiyah; Bachri, Bachtiar Syaiful; Sa’ida, Naili (International Journal of Emerging Technologies in Learning (iJET), 2021)
The development of science and technology during the Covid-19 pandemic re-quires universities to prepare their students to have collaborative and problem-solving skills through appropriate learning today, namely, integrating learning with online technology. This study aimed to determine the effectiveness of im-plementing collaborative problem-based learning (CPBL) integrated with online learning on student collaborative and problem-solving skills. The research meth-od used was quantitative with a post-test quasi-experimental design involving fourth-semester students in the Early Childhood Education Study Program, Uni-versitas Muhammadiyah Sidoarjo, Indonesia. The effectiveness of implementing CPBL integrated with online learning was analyzed primarily using the t-independent sample test. The study results showed that the implementation of CPBL integrated with online learning effectively improved students’ collaborative and problem-solving skills. This effectiveness especially occurs when construct-ing knowledge, looking for resolution strategies, and evaluating solutions in breakout rooms and collaborative forums and zoom meetings. Meanwhile, the study results recommend that CPBL integrated with online learning can be used as a solution and an essential study for academics to keep familiarizing and prac-ticing collaborative and problem-solving skills that are relatively difficult to im-prove during the Covid-19 pandemic.